Labour Subcontracting in the Construction Industries of Developing Countries: An Assessment from Two Perspectives - Wells, Jill (Penerbit Universiti Sains Malaysia, 2006)
The practice of employing labour through subcontractors (often referred to as the "outsourcing" of labour) is both long established and widespread in the construction industries of developing countries. Recent studies show that it is also increasing in both developing and developed countries. An assessment of the advantages of the practice from the viewpoint of the contractors and of the labour force, suggests it is unlikely to disappear. The paper goes on to explore the implications for the development of the construction industry, as well as for the welfare of the workers and the achievement of broader development objectives. It is concluded that interventions may be needed to deal with some of the negative repercussions, but they have to accept and build on current labour practices.